VEGF 165 b, an antiangiogenic VEGF-A isoform, binds and inhibits bevacizumab treatment in experimental colorectal carcinoma: balance of pro- and antiangiogenic VEGF-A isoforms has implications for therapy. - Varey, A; Rennel, E; Qiu, Y; Bevan, H; Perrin, R; Raffy, S; Dixon, A; Paraskeva, C; Zaccheo, O; Hassan, A; Harper, S; Bates, DO (2008)
Bevacizumab, an anti-vascular endothelial growth factor (VEGF-A) antibody, is used in metastatic colorectal carcinoma (CRC) treatment, but responses are unpredictable. Vascular endothelial growth factor is alternatively spliced to form proangiogenic VEGF(165) and antiangiogenic VEGF(165)b. Using isoform-specific enzyme-linked immunosorbent assay and quantitative polymerase chain reaction, we found that over 90% of the VEGF in normal colonic tissue was VEGF(xxx)b, but there was a variable upregulation of VEGF(xxx) and downregulation of VEGF(xxx)b in paired human CRC samples. Furthermore, cultured colonic adenoma cells expressed predominantly VEGF(xxx)b, whereas colonic carcinoma cells expressed predominantly VEGF(xxx). However, adenoma cells exposed to hypoxia switched their expression from predominantly VEGF(xxx)b to predominantly VEGF(xxx). VEGF(165)b overexpression in LS174t colon cancer cells inhibited colon carcinoma growth in mouse xenograft models. Western blotting and surface plasmon resonance showed that VEGF(165)b bound to bevacizumab with similar affinity as VEGF(165). However, although bevacizumab effectively inhibited the rapid growth of colon carcinomas expressing VEGF(165), it did not affect the slower growth of tumours from colonic carcinoma cells expressing VEGF(165)b. Both bevacizumab and anti-VEGF(165)b-specific antibodies were cytotoxic to colonic epithelial cells, but less so to colonic carcinoma cells. These results show that the balance of antiangiogenic to proangiogenic isoforms switches to a variable extent in CRC, regulates tumour growth rates and affects the sensitivity of tumours to bevacizumab by competitive binding. Together with the identification of an autocrine cytoprotective role for VEGF(165)b in colonic epithelial cells, these results indicate that bevacizumab treatment of human CRC may depend upon this balance of VEGF isoforms.